Implementing English as a Medium of Instruction: Qualitative Inquiry of Mathematics and Science Teachers - Dahal, Mukti Nath; Koirala, Navaraj (Academic Journal of Sukuna, 2025)
Abstract This study examines the views of public school teachers on pedagogical issues, including diverse learning styles, technology integration, facilitating students’ engagement in learning, and addressing social-emotional engagement of learners, as they implement English as a medium of instruction in Nepal. The paper focuses on the challenges and opportunities of shifting Nepali medium of instruction to English medium instruction. The study employed qualitative research to explore the subjective experiences of science and mathematics teachers. The participants of the study were eight teachers of Sundarharincha Municipality, Morang. An interview guideline was prepared to collect the information from the participants. Their experiences were subsequently analyzed and interpreted under explicit themes and sub-themes. The main findings of the study showed that the teachers were found to be positive towards the implementation of EMI; however, they have experienced the burden of implementing English as a medium of instruction. The school administration claimed to have adopted EMI, but still the medium of instruction used in the classrooms is Nepali due to the lack of language proficiency of teachers and students, insufficient resources of the schools, and the lack of preparation for shifting the medium. As a result, EMI is a kind of burden for the public-school teachers and students in the present context.